CLASSIFYING TRASH BIN BY SHAPE SCANNING AND SOLID WASTE PRESSING - VILCAHUAMAN-SANABRIA, RAUL (2024)
CURRENTLY, THE ISSUE OF SOLID WASTE IS CONSIDERED ONE OF THE BIGGEST PROBLEMS FACING HUMANITY SINCE LACK OF HYGIENE LEADS TO SERIOUS DISEASES THAT CAN LEAD TO DEATH. FOR THIS REASON, THIS PROJECT IS PROPOSED THAT PRIORITIZES PEOPLE'S HEALTH BY NOT GENERATING DIRECT CONTACT WITH THE GARBAGE DUMP AND PREVENTS THE DISPERSION OF GARBAGE WITH A PRESSING SYSTEM THAT, IN ADDITION TO HELPING THE ENVIRONMENT, IMPROVES THE LOGISTICS OF THE UNIVERSITY CITY WHICH IS THE STUDY SITE OF THIS PROJECT. THIS GARBAGE DEVICE THAT PRESSES SOLID WASTE USES A SET OF SENSORS THAT FACILITATE THE CLASSIFICATION OF SOLID WASTE, SUCH AS PLASTICS, CARDBOARD, ALUMINUM CANS, ETC. IN ADDITION, SOLAR PANELS ARE USED SINCE IT IS AN ENVIRONMENTALLY FRIENDLY MEANS AND GENERATES COST SAVINGS IN ELECTRICAL ENERGY CONSUMPTION. © 2024 IEEE.